2017
DOI: 10.1093/mnras/stx1270
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic crystal structure of magnetized neutron star crust

Abstract: Although crystallized neutron star crust is responsible for many fascinating observational phenomena, its actual microscopic structure in tremendous gravitational and magnetic fields is not understood. Here we show that in a non-uniform magnetic field, three-dimensional ionic Coulomb crystals comprising the crust may stretch or shrink while their electrostatic pressure becomes anisotropic. The pressure depends non-linearly on the magnitude of the stretch, so that a continuous magnetic field evolution may resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
(28 reference statements)
1
30
0
Order By: Relevance
“…Thus, an accurate knowledge of the crust strength is fundamental for NS physics and in this paper we analyse it, paying special attention to its anisotropy. Previous works in this field explored a shear deformation by MD simulation (Horowitz & Kadau 2009;Chugunov & Horowitz 2010Hoffman & Heyl 2012) and volume-conserving crystal stretching in two highly symmetric directions semianalytically (Baiko & Kozhberov 2017; Paper 1). Here we apply the approach proposed in the latter work to study stretching in arbitrary directions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an accurate knowledge of the crust strength is fundamental for NS physics and in this paper we analyse it, paying special attention to its anisotropy. Previous works in this field explored a shear deformation by MD simulation (Horowitz & Kadau 2009;Chugunov & Horowitz 2010Hoffman & Heyl 2012) and volume-conserving crystal stretching in two highly symmetric directions semianalytically (Baiko & Kozhberov 2017; Paper 1). Here we apply the approach proposed in the latter work to study stretching in arbitrary directions.…”
Section: Introductionmentioning
confidence: 99%
“…The bcc lattice which stretched along its main diagonal (in the direction of the nearest neighbour) is stable when 0.92 < c d1 < 1.13, where c d1 is the ratio of the length of the diagonal along the deformation to the length of the undeformed diagonal. 24 Stretched along the diagonal of the base of the elementary cell cube (towards the third nearest neighbour), the bcc lattice is stable when c d3 lies between 0.9 and 1.06, where c d3 is the similar ratio as in the previous case but for the base diagonal.…”
Section: Phonon Stabilitymentioning
confidence: 91%
“…It is widely done in Refs. 24,25 where it was found that no deformation can bring the bcc lattice to a state with a lower electrostatic energy. Thus, the bcc Coulomb lattice has the lowest electrostatic energy among all lattices under consideration.…”
Section: One-component Latticesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the bcc lattice can be turned into the fcc lattice by continuous deformation (Baiko & Kozhberov 2017). According to the linear mixing rule, µ eff of the binary fcc lattice is…”
Section: Binary Face-centered Cubic Latticementioning
confidence: 99%